Thermal Analysis of 150 Ah Lithium-Ion Battery Module and Its Liquid Cooling Plate - Gökmen, Yiğitalp; Gediz Ilis, Gamze (Avestia Publishing, 2025)
Effective cooling of lithium-ion battery modules has a critical role in the thermal stability and life span of the battery. This study investigated the thermal effects of two different water-cooling plate designs on the electrochemically modeled battery module. Therefore, heat generation values during 0.5C and 1.0C charging were generated by a 3D electrochemical cell model for a 150 Ah LFP prismatic battery. Then, the generated heat was transferred to the 11,250 Ah capacity battery module with a water cooling plate. Results show that the U-type channel layout provides more uniform temperature distribution and 1.86 – 2.69°C less temperature rise along the battery module. In addition, increasing the volume flow rate is more effective with a U-type channel layout than with parallel channels. In all cases, increasing the volume flow rate from 4 to 5 L•min-1 has the lowest decrease in temperature which is 0.5°C on average. © 2025 Elsevier B.V., All rights reserved.
10th World Congress on Momentum, Heat and Mass Transfer, MHMT 2025 -- Barcelona -- 330319
Keywords: Battery Cooling; Battery Thermal Management; CFD; Liquid Cooling Plate; Lithium-Ion Battery Module; Numerical Simulation; Thermal Analysis